STUDY OF PHYSICOCHEMICAL CHARACTERISTICS OF BIRD VALLEY’S QUARRY WATER PCMC, MAHARASHTRA - Kokcha, Shashikala; Chatrath, Harsha (Green Chemistry & Technology Letters, 2021)
Purpose of the study: The purpose of this study is to make sure that the Bird valley’s quarry water is suitable for drinking purposes or not and to monitor the seasonal variations in the physico-chemical parameters of this quarry water. Methodology: Water samples from the quarry were collected in clean and sterilized polyethylene bottles. Water samples were collected from different points and mixed together to get an integrated sample. Some of the selected physico-chemical parameters of the quarry water have been analyzed. Results were compared with standard limits of IS: 10500-2012. All the parameters were analyzed in the laboratory by using standard methods and techniques. Main Findings: As per the obtained results this quarry water contains a very large number of Coliforms detected in the months of September and December and in June month Coliform count was 33 CFU/ml. This overall result for coliform is making this quarry water unfit for domestic purposes. Applications of this study: This study helps us to understand the current condition of this quarry water and also enables us to know whether the quarry water is fit for drinking purposes. It also enables us to know whether this quarry water can be used for domestic purposes after the treatment. Novelty/Originality of this study: Bird valley’s quarry water has not been analyzed from this point of view till date. This study will help us to understand the present condition of the water.